ANALISIS PENANGANAN KREDIT BERMASALAH (NON PERFORMING LOAN) PADA PERUMDA BPR BANK GRESIK - Bilqis Tahta Maulida; Anita Handayani (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
This study aims to determine the handling of non-performing loans at the Perumda BPR Bank Gresik BPR. The reason for the research was to find out the number of non-performing loans that occurred in the Perumda BPR Bank Gresik over the last 5 years. The research uses descriptive research using a qualitative approach. The results of this study stated that there are many factors that cause non-performing loans such as internal bank factors, internal debtor factors and external factors of banks and debtors. The handling of non-performing loans is carried out by the Perumda BPR Bank Gresik with a process of rescheduling, requisition and realignment and is carried out by confiscating platforms from problem debtors.